The High-Rise Private Eyes : The Case of the Troublesome Turtle - Rylant, Cynthia; Karas, G. Brian (New York, 2001)
Bunny and Jack, animal detectives, investigate the disappearance of the balloons from the neighborhood toy store.
Keywords: Animals; Fiction; Balloons; Fiction; Football; Fiction; Mystery and detective stories